The role of forkhead box class O3A and SIRT1 gene variants in early-onset psoriasis - Suzan Demir Pektas; Gursoy Dogan; Tuba Gokdogan Edgunlu; Sevim Karakas-Celik; Esra Ermis; Nilgun Solak Tekin (Wolters Kluwer Medknow Publications, 2018)
Background: Psoriasis is a chronic inflammatory skin disorder, which is characterized by a heightened immunological response. Although the immunogenetics of this chronic inflammatory disorder is poorly understood, its expression is known to be dependent on proinflammatory cytokines. It is known that two distinct subtypes of chronic plaque psoriasis: Early-onset psoriasis (EOP) before the age of 40 years and late-onset psoriasis after the age of 40 years. Forkhead box class O3A (FOXO3A) is a transcription factor, which plays an important role in cell-cycle regulation, apoptosis, oxidative stress, and DNA repair. The silent information regulator (SIRT) is thought to have a role in skin disorders, including psoriasis, that are characterized by hyperproliferation and inflammation. Aim: The aim of this study was to investigate FOXO3A and SIRT1 gene polymorphisms in EOP. Methods: The study group consisted of 142 EOP patients and 123 unrelated healthy controls. FOXO3A polymorphisms were determined using the polymerase chain reaction (PCR)-restriction fragment length polymorphism method. SIRT1 gene polymorphisms were determined by PCR-confronting two-pair primers methods. Results: The FOXO3A rs4946936 and SIRT1 rs7069102 gene polymorphisms were positively correlated with EOP and disease severity. The GG genotype frequency of SIRT1 rs7069102 gene polymorphisms was increased in severe EOP. The CC frequency of FOXO3A rs4946936 was increased in EOP with nail disorders. Conclusion: The rs7069102 gene polymorphism of SIRT1 and rs4946936 polymorphism of FOXO3A are associated with early onset psoriasis; this may be responsible for increased keratinocyte proliferation in the pathogenesis of psoriasis and disease severity.